2021
DOI: 10.1177/13623613211035936
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, social isolation and the mental health of autistic people and their families: A qualitative study

Abstract: The COVID-19 pandemic and its policy responses have had a detrimental effect on millions of people’s mental health. Here, we investigate its impact on autistic people and their families using qualitative methods. Specifically, we addressed: how did autistic people experience an increase in social isolation during the initial lockdown? And how was their mental health impacted by lockdown? Autistic and non-autistic researchers conducted 144 semi-structured interviews with autistic adults (n = 44), parents of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
97
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 62 publications
18
97
1
4
Order By: Relevance
“…For all, the most reported challenge related to the social impact of the pandemic – over a quarter of both groups described how social disconnection had negatively affected them. This finding mirrors Pellicano et al’s (2021) research with Australian autistic people and goes against the stereotyped view that autistic people lack social interest and our findings support counter-arguments to the theoretical proposal that autistic people lack social motivation ( Jaswal and Akhtar, 2018 ). University can offer many social opportunities for autistic people, and while they may face challenges within social environments ( Scott and Sedgewick, 2021 ), we must find ways to enable autistic students to flourish socially in pandemic-adapted universities.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For all, the most reported challenge related to the social impact of the pandemic – over a quarter of both groups described how social disconnection had negatively affected them. This finding mirrors Pellicano et al’s (2021) research with Australian autistic people and goes against the stereotyped view that autistic people lack social interest and our findings support counter-arguments to the theoretical proposal that autistic people lack social motivation ( Jaswal and Akhtar, 2018 ). University can offer many social opportunities for autistic people, and while they may face challenges within social environments ( Scott and Sedgewick, 2021 ), we must find ways to enable autistic students to flourish socially in pandemic-adapted universities.…”
Section: Discussionsupporting
confidence: 81%
“…In a sample of 1,044 autistic adults from Belgium, Netherlands, and the United Kingdom, Oomen et al (2021) found increased depression and anxiety for autistic adults during the pandemic, as well as many missing social contact. Pellicano et al (2021) interviewed autistic adults, autistic young people, and parents (autistic and non-autistic), mostly from Australia, noting that although lockdowns brought fewer social pressures and reduced masking, many reported a negative impact of not being able to connect with other people, with mental health deteriorating. Together, these studies show the overall negative impact of the pandemic for autistic people, although we do not know much about autistic students’ experiences.…”
Section: Introductionmentioning
confidence: 99%
“…They reported high levels of psychological distress and disruption in their lives during the pandemic [ 31 , 34 , 37 , 38 , 39 , 40 , 41 , 42 ]. Some possible positive aspects of experiences during the pandemic have been also reported by parents of typically developing children [ 43 , 44 ] and caregivers of children with ASD [ 28 , 32 , 35 , 44 , 45 , 46 ]. These include the elimination of many daily pressures [ 32 , 45 ]; creating a more relaxing environment [ 28 ]; having more time to teach new skills, such as autonomy or house care-related skills [ 46 ]; having opportunities for increased family interaction and strengthening relationships [ 35 ]; developing positive characteristics such as appreciation, gratitude, and tolerance; and finding new hobbies [ 44 ].…”
Section: Introductionmentioning
confidence: 93%
“…Changes in daily structure, attempts to mitigate lost opportunities for children’s learning and social interactions, increased screen time, and reduced physical activities are factors that have been discussed as important stressors for parents [ 23 , 24 ]. The population of children with disabilities, in particular autism, gained special attention; both opinion [ 25 , 26 , 27 ] and research papers discussed the possible impact of the COVID-19 pandemic on individuals with ASD [ 28 , 29 , 30 , 31 , 32 , 33 ] and their families [ 28 , 31 , 32 , 34 , 35 ]. They suggested strategies for them to better accommodate to the situation.…”
Section: Introductionmentioning
confidence: 99%
“…Some people's mental health has been damaged by not being able to see people during COVID-19. Autistic people need support in many areas of life so they can keep mixing up, socializing and meeting their friends even through difficult times, like pandemics [10]. People with mental health conditions could be more significantly influenced by the emotional responses brought on by the COVID-19 epidemic, resulting in declining or deteriorating of an already existing mental health condition because of high vulnerability to stress compared with the general population [11].…”
Section: Discussionmentioning
confidence: 99%